2020
DOI: 10.1111/spsr.12392
|View full text |Cite
|
Sign up to set email alerts
|

When Do Men Represent Women’s Interests in Parliament? How the Presence of Women in Parliament Affects the Legislative Behavior of Male Politicians

Abstract: This paper analyzes the conditions affecting male Members of Parliaments’ (MPs) proclivity for representing women’s interests. It particularly explores whether the presence of female MPs has an effect on men’s parliamentary behavior. Three contrasting effects are discussed in the literature: (1) A spillover effect which postulates that men will become more likely to act on behalf of women if the number of female MPs increases, (2) a group‐threat effect which creates a hostile backlash among male MPs, or (3) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Kokkonen and Wängnerud (2017) conducted a survey of politicians in Swedish municipalities and found that the presence of women has a negative effect on male MPs’ willingness to act for women in the council. Similar results have been found by Höhmann (2020b), who shows that while male MPs in the German Bundestag are generally willing to act on behalf of women, they will leave this field to female MPs if the proportion of women in their respective PPG increases. Olofsdotter Stensota (2020) shows that male MPs’ personal backgrounds also affect their legislative priorities and their inclination to represent women‐specific issues.…”
Section: Male Mps and The Representation Of Women's Interestssupporting
confidence: 86%
See 1 more Smart Citation
“…Kokkonen and Wängnerud (2017) conducted a survey of politicians in Swedish municipalities and found that the presence of women has a negative effect on male MPs’ willingness to act for women in the council. Similar results have been found by Höhmann (2020b), who shows that while male MPs in the German Bundestag are generally willing to act on behalf of women, they will leave this field to female MPs if the proportion of women in their respective PPG increases. Olofsdotter Stensota (2020) shows that male MPs’ personal backgrounds also affect their legislative priorities and their inclination to represent women‐specific issues.…”
Section: Male Mps and The Representation Of Women's Interestssupporting
confidence: 86%
“…First, all models include the MPs’ party affiliation , to account for ideological differences in the MPs’ affinity to gender equality, as well as for general differences in the different parties’ electoral prospects and that of their candidates. Second, prior research has shown that the increased presence of women in parliament might negatively affect male MPs’ likelihood of representing women's interests (Höhmann 2020b). The analysis therefore controls for the s hare of female MPs in the respective male MP's party.…”
Section: Methods and Datamentioning
confidence: 99%
“…And, as there are more women in the body, they report less obligation to speak for women because this labor is distributed across them all, which may mean less collaboration on women’s issues (Beckwith and Cowell-Meyers 2007); again, a sign that marginalization decreasing would account for these results. It is also possible that as the share of women increase, so does their engagement with men in the body (Nugent 2019; but see Höhmann 2020), allowing more co-sponsorships across identity categories or men taking the lead. In this case, more women in the body may be associated with fewer co-sponsorships and less bill success.…”
Section: Women’s Successmentioning
confidence: 99%
“…Over time, men legislators learn about women's policy preferences and develop a higher level of awareness for women's concerns (Bratton, 2005, Flammang, 1985, Childs and Krook, 2006a. However, in parallel, a new logic of appropriateness emerges, according to which men should not speak for women, because women may speak for themselves in parliament (Höhmann 2020). In consequence, men face a situation of cognitive dissonance, in which two pieces of information that are linked to each other do not correspond (Festinger, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…First, this analysis constitutes the first time-series cross-sectional study that engages with the promotion of women's interests by men MPs. In contrast to previous scholarly work in the field that studied single legislatures over time (Höhmann, 2020, Höhmann andNugent, 2021), the comparative design allows this study to disentangle the effects of broader societal trends towards gender equality (Inglehart and Norris, 2003) and women's presence in parliament on the behavior of men MPs. Second, in this article, I apply a multi-dimensional, comprehensive understanding of substantive representation.…”
Section: Introductionmentioning
confidence: 99%